Impacto dinâmico da estratégia de marketing em dispositivos móveis no desempenho de uma empresa varejista - Costa, Milena Alves (2018)
The aim of this paper was to analyze the impact of the marketing strategy in mobile devices, through promotional and advertising publicity in offers aggregator app and social media, in company performance, which will be represented by the sales revenue, gross profit and number of sales. To achieve this goal, the data was analyzed in 91 days, from October 1st to December 31st of 2017, of a midsize supermarket, its social media and the visualizations of its content in an app. The analyses happened by an autoregressive modeling, method that has as an analyses tool result the generation of the impulse response function, that will provide the strategies elasticity in social media and app in performance. The results are: the visualizations of the app have direct effect on the number of sales, total sales and gross profit of the supermarket. The reach of posts (variable regarding to the social media), had effect only on the app, which demonstrates indirect impact in performance. It can be concluded that the communication channels integration in mobiles devices have a direct and indirect impact on the business performance, being a practicable alternative to the midsize retail companies invest in marketing.